Measuring and valuing health benefits for economic evaluation - Brazier, John; Ratcliffe, Julie; Salomon, Joshua A.; Tsuchiya, Aki (Oxford University Press, 2017)
"This new edition contains updated empirical examples and practical applications, which help to clarify the readers understanding of real world contexts. It features a glossary containing the common terms used by practitioners, and has been updated to cover new measures of health and wellbeing, such as ICECAP, ASCOT and AQOL. It takes into account new research into the social weighting of a QALY, the rising use of ordinal valuation techniques, use of the internet to collect data, and the use of health state utility values in cost effectiveness models.This is an ideal resource for anyone wishing to gain a specialised understanding of health benefit measurement in economic evaluation, especially those working in the fields of health economics, public sector economics, pharmacoeconomics, health services research, public health, and quality of life research."--Provided by publisher.